TRAJECTORY MODELING OF MARINE OIL SPILLS: CASE STUDY OF LACH HUYEN PORT, VIETNAM - D. Quang Tri; N. Cao Don; C. Yi Ching (Lowland Technology International, 2013)
In 2011, an oil spill occurred off Lach Huyen port in the Northeast of Vietnam, due to vessels collision. the result of collision caused pollution on wide area and surrounding areas. This paper was used MIKE 21 SA model to simulate oil spill transport with five scenarios. The results of simulation showed that spill trajectory and slick arrea depend on analysis hydraulic regime, wind direction and wave in the study area. This paper presents the model application for simulating spill scenarios. It helps in selecting eco-sensitive regions for preparedness and planning suitable response strategies whenever spill incident occurred.